Stickler Syndrome Type 1 with Short Stature and Atypical Ocular Manifestations - Manisha Goyal; Seema Kapoor; Shiro Ikegawa; Gen Nishimura (Case Reports in Pediatrics)
Stickler syndrome or hereditary progressive arthroophthalmopathy is a heterogeneous group of collagen tissue disorders, characterized by orofacial features, ophthalmological features (high myopia, vitreoretinal degeneration, retinal detachment, and presenile cataracts), hearing impairment, mild spondyloepiphyseal dysplasia, and/or early onset arthritis. Stickler syndrome type I (ocular form) is caused by mutation in the COL2A1 gene. Ptosis and uveitis are relatively rare ophthalmological manifestations of this syndrome. We report an Indian boy having 2710C>T mutation in COL2A1 gene demonstrating short stature, ptosis, and uveitis with Stickler syndrome.